High Diversity and Prevalence of Borrelia burgdorferi sensu lato in Wildlife Hosts, Domestic Animals, and Ticks in Yunnan Province, Southwestern China - He, Zhihai; Jiang, Baogui; Huang, Lin; Shao, Zongti; Zhang, Yun; Li, Yuqiong; Pu, Ennian; Duan, Xingde; Jiang, Hang; Wang, Jian; Yao, Mingguo; Wang, Fan; et al. (Frontiers in Microbiology, 2022)
Borrelia burgdorferi sensu lato (BBSL), the causative agent of Lyme disease, is commonly found in wild and domestic mammals and ticks worldwide. In China, human cases of Borrelia burgdorferi infections have been identified across a wide geographic range including Yunnan Province, but few studies have examined BBSL in reservoirs and vectors in southwestern China. Here we conducted a thorough and broad-range investigation of BBSL in small mammals, domestic mammals and ticks collected from 159 sample sites across 42 counties in Yunnan Province. DNA was extracted from spleen tissue of small mammals, blood from domestic mammals and homogenized ticks. Nested PCR targeting the 5S-23S rRNA intergenic spacer gene of BBSL was used for screening, with amplicons sequenced directly and analyzed using a BLAST algorithm. A total of 8,478 samples were collected, which were composed of 5,044 mammals belonging to 68 species, 1,927 livestock belonging to five species and 1, 507 ticks belonging to 14 species. Borrelia burgdorferi sensu lato was detected in 147 mammals (2.9%) from 30 different species, 20 of which represent the first reported detection in that species. A total of 52 (2.7%) livestock samples were positive for BBSL, with canines having the highest detection rate (6.3%, 43/687), and 103 ticks (6.8%) tested positive with high prevalence in Ixodes granulatus (44.2%, 23/52), Haemaphysalis nepalensi (33.3%, 3/9) and Haemaphysalis kolonini (19.0%, 31/163). Sequence analysis revealed six genospecies of BBSL including Borrelia afzelii, Borrelia burgdorferi sensu stricto, Borrelia japonica, Borrelia garinii, Borrelia sinica and Borrelia valaisiana. Significant differences in prevalence rates of BBSL were observed by species, landscape types and altitude. Our findings indicate a wide distribution of multiple endemic BBSL genospecies based on a large-scale survey within Yunnan, which underline the need to expand surveillance efforts for human in southwestern China.